Dielectric Behavior of Nickel-Zinc Dopped Hexagonal W-type Barium Ferrite - Abdulmajeed, Inaam M (Al-Nahrain Journal of Science, 2012)
A prepared compound of BaZn2-xNixFe16O27 (X=0, 0.5, 1, 1.5 and 2) is synthesized in polycrystalline form, using the stoichiometric mixture of oxides with conventional ceramic technique and characterized by X-ray diffraction. Analysis confirmed the presence of W-type hexagonal ferrite. The conductivity, dielectric constant and loss tangent (tanδ) were measured as a function of frequency taken between (100Hz-6MHz) at room temperatures and compositions. It was observed the ac conductivity is independent of frequency approximately for f < log 4.5 but if the frequency was greater than previous values then the conductivity increases strongly with frequency for all compositions, the electrical mechanism was explained in terms of the electron hopping mode. Moreover, the dielectric constant and dielectric loss factor decrease with frequency of applied electric field.